Setting of the 2560 MA Qorqut Granite Complex in the Archean Crustal Evolution of Southern West Greenland - Nutman, Allen P; Hiess, Joe; Friend, Clark R L (Research Online, 2010)
The Archean gneiss complex of West Greenland contains packages of unrelated rocks created during relatively short periods of time in arc-like magmatic environments, and having similarities to rocks formed at Phanerozoic convergent plate boundaries. The terranes of new Archean crust were amalgamated by collisional orogeny and then partitioned by post-assembly tectonic processes. Having summarized the origin of West Greenland Archean crust in arc-like environments, this paper then focuses on new data concerning the latest Neoarchean post terrane-assembly "intra-continental" tectonic and magmatic evolution of the region. Following the youngest documented high pressure metamorphism in a clockwise P-T-t loop at 2650 Ma, attributed to tectonic thickening of the crust, there is in West Greenland a 150 million year record of intermittent production of crustally-derived granite, shearing and folding under amphibolite facies conditions. This is exemplified by the SSW-NNE orientated Neoarchean Qorqut Granite Complex (QGC) which forms a myriad of closely spaced coeval sheets NE of Nuuk town. SHRIMP U-Pb zircon dating of a homogeneous gray granite sheet gives a magmatic age of 2561 + 11 Ma, with 3800 to 3600 and 3070 to 2970 Ma zircon xenocrysts. The >40 km long Fjringehavn straight belt, a lower amphibolite-facies vertical shear zone, runs from the QGC's SE margin and contains strongly deformed granite sheets with a U-Pb zircon age of 2565 + 8 Ma but is cut by undeformed granite sheets dated at 2555 + 12 Ma. The >60 km long Ivisaartoq fault consisting of lowermost amphibolite-facies mylonite runs from the northwestern end of the main mass of granite. It formed post-2630 Ma, because granites of that age are truncated by it. Near the QGC's northeastern extent, 2559 + 3 Ma granitic lithons in a folded mylonite are cut by 2521 + 72 Ma granite sheets. At a deep structural level at the northern end of the QGC, deformed granitic neosomes give ages of 2567 + 9 and 2563 + 5 Ma. Therefore, at 2560 Ma, the ages within error for strongly deformed to non-deformed granite bodies shows that the QGC is not a largely post-kinematic intrusion as previously thought, but was coeval with lowermost amphibolite-facies metamorphism and shear zones with an important strike slip component, late in the development of regional non-cylindrical upright folds. The main body of the QGC appears to be essentially post-kinematic only because it was emplaced in a node of dilation during the heterogeneous predominantly strike slip deformation. Melting at this node may have been triggered by meteoric water percolating down dilational fractures, causing metasomatism. Melting of these altered rocks gave rise to the low 18O signature of QGC igneous zircons. Due to the hydrous nature of the melting event, the QGC was emplaced immediately above its migmatitic generation zone. These late Neoarchean shear zones of the Nuuk region partition and disrupt the earlier-formed mosaic of amalgamated terranes of unrelated rocks. Such tectonic patterns are seen more recently, for example in Holocene Asian intra-continental tectonics along the north side of the Himalayas.